The Influence Of Organizational Culture, Work Discipline, And Organizational Citizenship Behavior On Organizational Commitment - Suherdi, Suherdi; Ahmad, Ahmad (BIMA Journal (Business, Management, & Accounting Journal), 2023)
This study aims to examine the influence of organizational culture, work discipline, and organizational citizenship behavior on organizational commitment and can make a theoretical and practical contribution to understanding the concept of organizational commitment. Â This research was conducted in five sub-districts in the Southern Region, Lebak Regency, and Banten Province. Meanwhile, the research period was from February to May 2020. The random sampling technique was used in this study, and the total number of respondents was 66. Â This study uses a quantitative survey research method using regression analysis techniques using SPSS version 20 software. Employee organizational commitment will increase as a result of organizational citizenship behavior.